MOS 2013 study guide for Microsoft Word Expert - Pierce, John 1954- (Microsoft Press, 2013)
Designed to help you practice and prepare for the 2013 PowerPoint Microsoft Office Specialist (MOS) exam, this all-in-one study guide features: full, objective-by-objective exam coverage; easy-to-follow procedures and illustrations to review essential skills; hands-on practice tasks to apply what you've learned. --
Print version record
Keywords: Microsoft Word -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Microsoft software -- Study guides -- Examinations; Microsoft Word / Examinations / Study guides; Microsoft Word; Logiciels Microsoft; Examens; Guides de l'étudiant; COMPUTERS; Programming; Microsoft; COMPUTERS; Data Processing; Electronic data processing personnel; Certification; Examinations; Microsoft software; Examinations; Study guides